Documentation of Wild Leafy Vegetable Plants of Chitwan, Nepal - Das, Manoj Kumar Lal (BMC Journal of Scientific Research, 2022)
Wild leafy vegetables are an important source of carbohydrates, proteins, minerals and fibers. Local people of Chitwan rely on wild leafy vegetables. Knowledge of wild leafy vegetables is part of traditional practice. This paper revealed total 38 plant species belonging to 32 Genera under 30 families which are consumed by local inhabitants of Chitwan. Out of 38 plants species consumed as leafy vegetable, 26 taxa were herbs, 6 species are climbers, 5 plant species as to trees and only one was climbers. The harvesting season of leafy vegetables are variable. 15 leafy vegetables plants were harvested during rainy season, 8 spp. were harvested in summer season. 12 plant species were harvested throughout the year. Similarly; 32 plant species were used for vegetables; 3 spp. were used for spices. A few spp. was consumed as raw, pickle and topping purpose.